Rendi Apriansyah S.H - rendi apriansyah; Heru Widodo (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2020)
ABSTRACT In article 303 of Book II of the Criminal Code (Penal Code), Gambling is classified as a crime. The occurrence of gambling crime is not solely due to society that is not lawful and violate the existing legal norms in society, but all that can not be separated also from the system of tribal tradition or a particular area. Gambling that for some people only used as a regular game at the tongkrongan while filling free time, is now a great game that can be risking property and even sometimes can be up to risk your life. Gambling practices in Tajen held by certain groups of people in Bali are legally in violation of the Criminal Code, Article 303. Police have done their best to dissolve either persuasively or repressively, in fact the tajen here and there are still held, if the tajen is stopped should grow from all levels of society itself, the Police will not be able to stop to zero because Tajen it is their habit and custom according to the law is difficult to change takes a very long time and must remain continuous conducted by all public figures and community itself and Relevant Government Agencies. Keywords: Gambling, Sociology, Tajen